Derecho a la igualdad y remuneración equitativa - Zuta Palacios, Karla (2019)
It is known that gender pay gap is a worldwide problem. Even though it is now a lot smaller than it used to be, there is still a lot to improve. In this context, the present article analyzes the legal treatment that this situation currently receives in Peru, focusing on equal pay and treatment within labour relationships. Its arguments are reinforced by national and international doctrine and jurisprudence. As a result of this analysis, the author details the criterion that are to be followed by judges and government inspectors, when determining the validity of unequal payment in certain cases. This criterion can also help distinguishing those cases in which the employer has committed a hostile or discriminating act.